(3JbfjGJ GdeMGSHI GdYGeI hab GdfXGe GdeMGSHj GdeGdj GdLOjO (Bscf :s (3GdEWGQ GdfXQj (B/s - (3WQWGQ, CMeOs ((3GdLRGFQ(B: s (3LShQ(B, s, 2018)
(3LGA aj Wj gPG GdcJGH cjajI JfWPXje GdYed GdeMGSHj hab GdfXGe GdeMGSHj GdeGdj GdLOjO, HeG ajg GdeYGdLI GdeMGSHjI hab (Bscf(3hcPdc GdJMdjd GdeMGSHj ddMSGHGJ, eY OQGSI MGdI eDSSI PGJ fTGW NOej aj eLGd GdHfGA hGdCTZGd GdYehejI ef JbOje YGe ddeDSSI, HGdGVGaI Edi JbOje GdbhGFe GdeGdjI GdNGUI HGdeDSSI(B.s
(3eQGLY U(B.249s